Policy Implementation of Smoke-Free Areas in Local Government Bureaucracy: Evidence from Tegal Regency, Indonesia - Jevon Muhammad Bernessa; Sri Sutjiatmi; Akhmad Habibullah (Jurnal Kebijakan Publik, 2026)
This study analyzes the implementation of the Smoke-Free Area Policy within the Regional Government of Tegal Regency based on Tegal Regency Regional Regulation Number 4 of 2022. The novelty of this study lies in its focus on smoke-free policy implementation within the regional bureaucratic environment, particularly in examining how regulation is translated into institutional practice, official compliance, and internal supervision mechanisms. This research employs a descriptive-analytical qualitative approach, with data collected through interviews, observations, and documentation at several regional government agencies. The analysis applies Edward III’s policy implementation theory, covering communication, resources, implementer disposition, and bureaucratic structure, supported by NVivo 12 through the Explore Diagram feature. The findings show that policy implementation has not been optimal because communication remains formal, resources are not supported by consistent supervision, compliance still depends on individual awareness, and the bureaucratic structure lacks internal procedures and measurable sanction mechanisms. This study highlights the need to strengthen socialization, optimize the Smoke-Free Area Task Force, promote leadership role modeling, prepare technical guidelines, and enforce regulations.